Modified graphene silane composite binder as well as preparation method and application thereof
By modifying graphene silane composite adhesive, combined with a specific ratio of silane coupling agent, fluorinated silane and conductive agent, the problem of insufficient adhesion and conductivity of existing silane coupling agents when bonding silicone rubber to metal materials is solved, efficient bonding between metal and silicone rubber is achieved, and conductivity and weather resistance are improved.
Patent Information
- Application Number
- CN202411783503.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing silane coupling agents have poor adhesion and poor conductivity when bonding silicone rubber to metal materials, and cannot meet the needs of bonding semiconductor silicone rubber to metal locking rings in high-voltage cable accessories.
Modified graphene silane composite binder is used, which consists of 10-20% silane coupling agent, 5-10% fluorinated silane, 4-8% conductive agent and balance as solvents. The silane coupling agent includes γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilpropylmethacrylic acid and octamethylcyclotetrasiloxane in a specific mass ratio, and the conductive agent includes reduced graphene oxide and carbon nanotubes.
When the modified graphene silane composite adhesive bonds significantly improve adhesion, conductivity, weather resistance and chemical resistance when bonding metals and silicone rubbers, making them more applicable on different metal surfaces.
Smart Images

Figure BDA0005173381250000081 
Figure BDA0005173381250000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal bonding, and in particular to a modified graphene-silane composite adhesive and a preparation method and application thereof. Background Art
[0002] Silicone rubber is widely used in various industrial fields due to its excellent elasticity, high and low temperature resistance, chemical corrosion resistance and other characteristics. However, the adhesion between silicone rubber and metal materials such as copper, aluminum and other materials is poor, which leads to limitations in practical applications. In the prior art, a coupling agent is usually coated on the metal surface so that its two ends are cross-linked with silicone rubber and metal respectively to enhance the adhesion between silicone rubber and metal materials. However, the existing silane coupling agents are still insufficient in terms of bonding strength, chemical resistance and weather resistance. At the same time, the existing silane coupling agents are not conductive, and the semi-conductive silicone rubber of high-voltage cable accessories needs to be able to achieve low resistivity when bonding with the metal locking ring. Therefore, it is particularly important to provide a modified silane coupling agent that has both high bonding performance and conductivity. Summary of the invention
[0003] The main purpose of the present invention is to provide a modified graphene silane composite adhesive and a preparation method and application thereof, so as to solve the problem of poor adhesion and poor conductivity of silane coupling agents in the prior art when bonding silicone rubber and metal materials.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a modified graphene silane composite adhesive is provided, which comprises, by mass fraction, 10-20% of a silane coupling agent, 5-10% of a fluorinated silane, 4-8% of a conductive agent, and the remainder is a solvent; wherein the silane coupling agent comprises γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the four is (8-10):(1-3):(1-3):(1-3).
[0005] Furthermore, in the modified graphene silane composite binder, the content of the silane coupling agent is 11-19%, the content of the fluorinated silane is 6-10%, the content of the conductive agent is 5-8%, and the balance is the solvent.
[0006] Furthermore, in the silane coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropylmethacrylate and octamethylcyclotetrasiloxane is (8-10):(1-3):(1-3):3.
[0007] Furthermore, the fluorinated silane is 3-fluoropropyltrimethoxysilane.
[0008] Furthermore, the conductive agent includes reduced graphene oxide and carbon nanotubes, and the mass ratio of the two is (4-6): (1-2).
[0009] Furthermore, the particle size of the reduced graphene oxide is 0.5-5 μm.
[0010] Furthermore, the diameter of the carbon nanotube is 1-50 nm.
[0011] Furthermore, the solvent includes at least one of n-heptane and ethyl acetate.
[0012] Furthermore, the solvent is a mixed solution of n-heptane and ethyl acetate, and the mass ratio of the two is (50-60): (50-40).
[0013] According to another aspect of the present invention, there is provided a method for preparing the modified graphene silane composite adhesive provided in the first aspect, comprising the following steps: mixing a silane coupling agent, a fluorinated silane, a conductive agent and a remainder of a solvent to obtain a modified graphene silane composite adhesive.
[0014] Furthermore, the mixing method is ultrasonic dispersion, the frequency of ultrasonic dispersion is 5 to 20 KHz, and the time of ultrasonic dispersion is 1 to 3 hours.
[0015] According to a third aspect of the present invention, there is provided an application of the modified graphene silane composite adhesive provided in the first aspect or the modified graphene silane composite adhesive obtained by the preparation method provided in the second aspect in metal bonding.
[0016] By applying the technical solution of the present invention, the present application uses a specific mass ratio of silane coupling agent, fluorinated silane and conductive agent to cooperate with each other, so that when the modified graphene silane composite adhesive is bonded to metal and silicone rubber, the bonding ability of the two ends with the metal and silicone rubber is enhanced, thereby improving the bonding between the metal and the silicone rubber, and at the same time, the metal and the silicone rubber can have excellent conductivity, weather resistance and chemical resistance. In addition, the silane coupling agent formed by the cooperation of γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilyl propyl methacrylate and octamethylcyclotetrasiloxane in a specific mass ratio further improves the bonding between the metal and the silicone rubber. And by utilizing the difference in the structure of each component in the silane coupling agent, the silane coupling agent can form a stable chemical bond with different metal surfaces, further expanding the applicability of the modified graphene silane composite adhesive on different metal surfaces. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As analyzed in the background technology of this application, the silane coupling agent in the prior art has the problems of poor adhesion and poor conductivity when bonding silicone rubber and metal materials. In order to solve this problem, this application provides a modified graphene silane composite adhesive and its preparation method and application.
[0019] In a typical embodiment of the present application, a modified graphene silane composite adhesive is provided, which comprises, by mass fraction, 10-20% silane coupling agent, 5-10% fluorinated silane, 4-8% conductive agent, and the remainder is solvent; wherein the silane coupling agent comprises γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the four is (8-10):(1-3):(1-3):(1-3).
[0020] This application uses a specific mass ratio of silane coupling agent, fluorinated silane and conductive agent to cooperate with each other, so that when the modified graphene silane composite adhesive is bonded to metal and silicone rubber, the bonding ability of the two ends with the metal and silicone rubber is enhanced, thereby improving the bonding between the metal and the silicone rubber, and at the same time, the metal and the silicone rubber have excellent conductivity, weather resistance and chemical resistance. In addition, the silane coupling agent formed by the cooperation of γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilyl propyl methacrylate and octamethylcyclotetrasiloxane in a specific mass ratio further improves the bonding between the metal and the silicone rubber. And by utilizing the differences in the structures of the components in the silane coupling agent, the silane coupling agent can form a stable chemical bond with different metal surfaces, further expanding the applicability of the modified graphene silane composite adhesive on different metal surfaces.
[0021] Typically but not restrictively, by mass fraction, the content of silane coupling agent in the modified graphene silane composite binder is 10%, 11%, 14%, 16%, 19%, 20% or a range consisting of any two values; the content of fluorinated silane is 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two values; the content of conductive agent is 4%, 5%, 6%, 7%, 8% or a range consisting of any two values.
[0022] Typically but not limitatively, the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent provided in the present application is 8:1.5:1.5:1, 8:1:3:3, 9:2:1:2, 10:3:1:1 or a range consisting of any two values.
[0023] It should be noted that the silane coupling agent in the present application does not include fluorinated silane.
[0024] In some embodiments, in the modified graphene silane composite adhesive, the content of silane coupling agent is 11-19%, the content of fluorinated silane is 6-10%, the content of conductive agent is 5-8%, and the balance is solvent, so as to further enhance the adhesion and conductivity of the modified graphene silane composite adhesive.
[0025] In some embodiments, in the silane coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane is (8-10):(1-3):(1-3):3, so as to further enhance the adhesion of the modified graphene silane composite adhesive.
[0026] In order to further enhance the weather resistance and chemical resistance of the modified graphene silane composite binder, the fluorinated silane is preferably 3-fluoropropyltrimethoxysilane.
[0027] In some embodiments, the conductive agent includes reduced graphene oxide and carbon nanotubes, and the mass ratio of the two is (4-6): (1-2). The more polar groups on the surface of reduced graphene oxide can promote the combination of reduced graphene oxide and silane coupling agent without stratification, thereby allowing the modified graphene silane composite adhesive to form a stable and continuous solution, further improving the conductivity. The synergistic conductive effect formed by the synergistic interaction of reduced graphene oxide and carbon nanotubes in a specific mass ratio further increases the conductivity of the modified graphene silane composite adhesive, and a higher conductive effect can be achieved at a lower amount of conductive agent added. In addition, the mechanical properties and thermal conductivity of the metal and silicone rubber bonding interface can be further improved, further enhancing the bonding strength.
[0028] Typically but not limitatively, in the conductive agent provided in the present application, the mass ratio of reduced graphene oxide to carbon nanotubes is, for example, 4:1, 4:2, 5:1.5, 6:1, 6:2 or a range consisting of any two values.
[0029] In the present application, the reduced graphene oxide can be purchased from the market (such as: Beijing Meiston Technology Development Co., Ltd., product model SY-rGO-S), or prepared in the following manner, the preparation method comprising the following steps: Step (1), providing natural graphene, using a mixed solution of potassium sulfate and sulfuric acid at 50°C to perform a mild oxidation treatment on the natural graphene to oxidize part of the graphene to obtain graphene oxide. Mild oxidation treatment can not only introduce polar functional groups such as hydroxyl groups and carboxyl groups on the graphene surface to ensure subsequent chemical reaction activity, but also reduce the damage to the graphene sheet structure caused by excessive oxidation. Step (2), heating the graphene oxide to 400°C under nitrogen protection for reduction treatment to obtain reduced graphene. The reduction treatment is to restore partial conductivity, ensure that the graphene material has high conductivity, reduce defects in graphite, and improve the mechanical strength of the graphene material. Step (3), using plasma treatment technology to perform surface activation on the reduced graphene to obtain reduced graphene oxide. Plasma treatment technology can make the surface of reduced graphene oxide have more reaction sites. These reaction sites help the silane coupling agent to form a stable chemical bond with the surface of reduced graphene oxide, thereby improving the dispersibility and stability of reduced graphene oxide.
[0030] In order to further evenly disperse the reduced graphene oxide in the silane coupling agent and avoid agglomeration and sedimentation caused by excessively large particle size of the reduced graphene oxide, thereby affecting the conductivity of the modified graphene-silane composite binder, the particle size of the modified graphene is preferably 0.5-5 um.
[0031] In order to further improve the conductivity of the carbon nanotubes, the diameter of the carbon nanotubes is preferably 1-50 nm.
[0032] Typically but not limiting, the particle size of the reduced graphene oxide is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range consisting of any two values; the diameter of the carbon nanotube is 1 nm, 5 nm 10 nm, 20 nm, 30 nm, 40 nm, 50 nm or a range consisting of any two values.
[0033] When the number of polar groups on the surface of reduced graphene oxide is small, it is easy to cause the modified graphene and the silane coupling agent to be delaminated, which reduces the conductivity. In order to make the reduced graphene oxide and the silane coupling agent better combined and evenly dispersed, in practical applications, the number of polar groups on the surface of reduced graphene oxide can be adaptively increased to further improve the conductivity of the modified graphene silane composite binder.
[0034] In order to further promote the dissolution of the silane coupling agent, fluorinated silane and conductive agent in the solvent and achieve green environmental protection, an organic compound is preferably used as the solvent, and the solvent includes any one or more of n-heptane and ethyl acetate.
[0035] In order to further promote the dissolution and dispersion of the silane coupling agent, fluorinated silane and conductive agent, the solvent is preferably a mixture of n-heptane and ethyl acetate, and the mass ratio of the two is (50-60): (50-40).
[0036] Typically but not limiting, the mass ratio of n-heptane to ethyl acetate in the solvent is 50:50, 52:48, 54:46, 56:44, 58:42, 60:40 or a range consisting of any two of these values.
[0037] In actual application, those skilled in the art may appropriately add the above-mentioned solvent to the modified graphene silane composite binder for dilution according to the actual application environment or purpose to ensure the actual use effect of the product.
[0038] In another typical embodiment of the present application, a method for preparing the modified graphene silane composite adhesive provided in the above-mentioned first typical embodiment is provided, comprising the following steps: mixing a silane coupling agent, a fluorinated silane, a conductive agent and a remaining amount of a solvent to obtain a modified graphene silane composite adhesive.
[0039] The preparation method provided in the present application is simple to operate and suitable for industrial production.
[0040] In order to further promote the dissolution and dispersion of each component in the solvent, the preferred mixing method is ultrasonic dispersion, the frequency of ultrasonic dispersion is 5 to 20 KHz, and the time of ultrasonic dispersion is 1 to 3 hours.
[0041] In a third typical embodiment of the present application, there is provided an application of the modified graphene silane composite adhesive provided in the first typical embodiment or the modified graphene silane composite adhesive obtained by the preparation method provided in the second typical embodiment in metal bonding.
[0042] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0043] It should be noted that “%” in the following examples and comparative examples refers to “wt %”.
[0044] Example 1
[0045] This embodiment provides a modified graphene silane composite binder, which includes 12% silane coupling agent, 6% fluorinated silane, 5% conductive agent, and the remainder is solvent, calculated by mass fraction. Among them, the silane coupling agent includes γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the four is 8:1.5:1.5:1. The fluorinated silane is 3-fluoropropyl trimethoxysilane; the conductive agent includes reduced graphene oxide (purchased from Beijing Meiston Technology Development Co., Ltd., product model SY-rGO-S) and carbon nanotubes (particle size 30nm), and the mass ratio of the two is 4:1; the solvent is a mixed solution of n-heptane and ethyl acetate, and the mass ratio of the two is 52:48.
[0046] The modified graphene silane composite binder is prepared according to the following steps: γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylic acid, octamethylcyclotetrasiloxane and 50wt% solvent are mixed, and ultrasonic dispersion technology is used to uniformly mix, the frequency of ultrasonic dispersion is 10KHz, and the time of ultrasonic dispersion is 1.5h. Then, reduced graphene oxide, carbon nanotubes, and 3-fluoropropyl trimethoxysilane are added in sequence, and ultrasonic dispersion technology is used to uniformly disperse the components under the conditions of ultrasonic dispersion frequency of 10KHz and ultrasonic dispersion time of 1.5h, and finally 50wt% solvent is added, and stirred evenly to obtain the modified graphene silane composite binder.
[0047] Example 2
[0048] The difference between Example 2 and Example 1 is that the content of each component in the modified graphene silane composite adhesive is adjusted, calculated by mass fraction, so that the modified graphene silane composite adhesive includes 10% silane coupling agent, 10% fluorinated silane, 8% conductive agent, and the balance is solvent.
[0049] Example 3
[0050] The difference between Example 3 and Example 1 is that the content of each component in the modified graphene silane composite adhesive is adjusted, calculated by mass fraction, so that the modified graphene silane composite adhesive includes 20% silane coupling agent, 5% fluorinated silane, 4% conductive agent, and the balance is solvent.
[0051] Example 4
[0052] The difference between Example 4 and Example 1 is that the content of each component in the modified graphene silane composite adhesive is adjusted, calculated by mass fraction, so that the modified graphene silane composite adhesive includes 11% silane coupling agent, 10% fluorinated silane, 8% conductive agent, and the balance is solvent.
[0053] Example 5
[0054] The difference between Example 5 and Example 1 is that the content of each component in the modified graphene silane composite binder is adjusted, calculated by mass fraction, so that the modified graphene silane composite binder includes 19% silane coupling agent, 6% fluorinated silane, 5% conductive agent, and the balance is solvent.
[0055] Example 6
[0056] The difference between Example 6 and Example 1 is that the mass ratio of the components in the silane coupling agent is adjusted so that the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent is 8:1:3:3.
[0057] Example 7
[0058] The difference between Example 7 and Example 1 is that the mass ratio of the components in the silane coupling agent is adjusted so that the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent is 10:3:1:1.
[0059] Example 8
[0060] The difference between Example 8 and Example 1 is that the mass ratio of each component in the conductive agent is adjusted so that the mass ratio of the modified graphene and the carbon nanotubes in the conductive agent is 4:2.
[0061] Example 9
[0062] The difference between Example 9 and Example 1 is that the mass ratio of each component in the conductive agent is adjusted so that the mass ratio of the modified graphene and the carbon nanotubes in the conductive agent is 6:1.
[0063] Example 10
[0064] The difference between Example 10 and Example 1 is that the mass ratio of each component in the conductive agent is adjusted so that the mass ratio of the modified graphene and the carbon nanotubes in the conductive agent is 7:0.5.
[0065] Embodiment 11
[0066] The difference between Example 11 and Example 1 is that the mass ratio of each component in the conductive agent is adjusted so that the mass ratio of the modified graphene and the carbon nanotubes in the conductive agent is 2:4.
[0067] Example 12
[0068] The difference between Example 12 and Example 1 is that the modified graphene in the conductive agent is removed, so that the conductive agent is carbon nanotubes.
[0069] Embodiment 13
[0070] The difference between Example 13 and Example 1 is that the carbon nanotubes in the conductive agent are removed, so that the conductive agent is modified graphene.
[0071] Comparative Example 1
[0072] The difference between Comparative Example 1 and Example 1 is that the content of each component in the modified graphene silane composite binder is adjusted, calculated by mass fraction, so that the modified graphene silane composite binder includes 7% silane coupling agent, 13% fluorinated silane, 9% conductive agent, and the balance is solvent.
[0073] Comparative Example 2
[0074] The difference between Comparative Example 2 and Example 1 is that the content of each component in the modified graphene silane composite binder is adjusted, calculated by mass fraction, so that the modified graphene silane composite binder includes 23% silane coupling agent, 2% fluorinated silane, 2% conductive agent, and the balance is solvent.
[0075] Comparative Example 3
[0076] The difference between Comparative Example 3 and Example 1 is that the mass ratio of the components in the silane coupling agent is adjusted so that the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent is 12:0.5:0.5:4.
[0077] Comparative Example 4
[0078] The difference between Comparative Example 4 and Example 1 is that the mass ratio of the components in the silane coupling agent is adjusted so that the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent is 6:4:5:0.5.
[0079] Comparative Example 5
[0080] The difference between Comparative Example 5 and Example 1 is that the tetraethoxysilane in the silane coupling agent is removed, so that the silane coupling agent includes γ-aminopropyltriethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the three is 8:1.5:2.5.
[0081] Comparative Example 6
[0082] The difference between Comparative Example 6 and Example 1 is that the trimethoxysilylpropyl methacrylate in the silane coupling agent is removed, so that the silane coupling agent includes γ-aminopropyltriethoxysilane, tetraethoxysilane and octamethylcyclotetrasiloxane, and the mass ratio of the three is 8.5:2:1.5.
[0083] Comparative Example 7
[0084] The difference between Comparative Example 7 and Example 1 is that trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane in the silane coupling agent are removed, so that the silane coupling agent includes γ-aminopropyltriethoxysilane and tetraethoxysilane, and the mass ratio of the two is 9:3.
[0085] Test example
[0086] The modified graphene silane composite adhesive sample provided in the examples and comparative examples of the present application is applied to the surface of the copper metal sheet and naturally air-dried at room temperature to obtain the copper metal sheet to be bonded. The thickness of the modified graphene silane composite adhesive coating layer on the copper metal sheet to be bonded is 0.1 mm. Subsequently, a semi-conductive liquid silicone rubber (model 1523) is poured on the copper metal sheet to be bonded to obtain a silicone rubber and copper metal composite sheet to be tested, and its tensile shear strength and volume resistivity are tested. The results are shown in Table 1.
[0087] Tensile shear strength test method: Test in accordance with the national standard GB / T 13936-2014.
[0088] Volume resistivity test method: refer to GB / T 3048.3 for testing.
[0089] Table 1
[0090]
[0091]
[0092] From the experimental data of Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2, it can be seen that when the modified graphene silane composite binder includes 10-20wt% silane coupling agent, 5-10wt% fluorinated silane, 4-8wt% conductive agent, and the balance is solvent, the tensile shear strength between the metal and the silicone rubber is large, and the volume resistivity of the modified graphene silane composite binder is small, indicating that the adhesion and conductivity between the metal and the silicone rubber are strong. When the components or proportions of the modified graphene silane composite binder are changed, it is impossible to simultaneously take into account excellent adhesion and conductivity.
[0093] From the experimental data of Examples 6 and 7 and Comparative Examples 3, 4, 5, 6 and 7, it can be seen that when the silane coupling agent includes γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the four is (8-10): (1-3): (1-3): (1-3), the tensile shear strength between the metal and the silicone rubber is large, and the volume resistivity of the modified graphene silane composite adhesive is small, indicating that the adhesion and conductivity between the metal and the silicone rubber are strong. When the components or proportions of the silane coupling agent are changed, the tensile shear strength between the metal and the silicone rubber decreases, indicating that the adhesion between the metal and the silicone rubber is reduced.
[0094] It can be seen from the experimental data of Examples 8, 9 and Examples 10, 11, 12, and 13 that when the conductive agent includes reduced graphene oxide and carbon nanotubes, and the mass ratio of the two is (4-6): (1-2), the tensile shear strength between the metal and the silicone rubber is large, and the volume resistivity of the modified graphene silane composite adhesive is small, indicating that the adhesion and conductivity between the metal and the silicone rubber are strong. When the component or ratio of the conductive agent is changed, the volume resistivity of the modified graphene silane composite adhesive increases, indicating that the conductivity between the metal and the silicone rubber is reduced.
[0095] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0096] This application uses a specific mass ratio of silane coupling agent, fluorinated silane and conductive agent to cooperate with each other, so that when the modified graphene silane composite adhesive is bonded to metal and silicone rubber, the bonding ability of the two ends with the metal and silicone rubber is enhanced, thereby improving the bonding between the metal and the silicone rubber, and at the same time, the metal and the silicone rubber have excellent conductivity, weather resistance and chemical resistance. In addition, the silane coupling agent formed by the cooperation of γ-aminopropyl triethoxysilane, tetraethoxysilane, trimethoxysilyl propyl methacrylate and octamethylcyclotetrasiloxane in a specific mass ratio further improves the bonding between the metal and the silicone rubber. And by utilizing the differences in the structures of the components in the silane coupling agent, the silane coupling agent can form a stable chemical bond with different metal surfaces, further expanding the applicability of the modified graphene silane composite adhesive on different metal surfaces.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified graphene silane composite binder, characterized in that: Measured by mass fraction, the modified graphene silane composite adhesive includes 10-20% silane coupling agent, 5-10% fluorinated silane, 4-8% conductive agent, and the balance is solvent; wherein the silane coupling agent includes γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropyl methacrylate and octamethylcyclotetrasiloxane, and the mass ratio of the four is (8-10):(1-3):(1-3):(1-3).
2. The modified graphene silane composite binder according to claim 1, characterized in that: Calculated by mass fraction, in the modified graphene silane composite binder, the content of the silane coupling agent is 11-19%, the content of the fluorinated silane is 6-10%, the content of the conductive agent is 5-8%, and the balance is solvent.
3. The modified graphene silane composite binder according to claim 1 or 2, characterized in that: In the silane coupling agent, the mass ratio of γ-aminopropyltriethoxysilane, tetraethoxysilane, trimethoxysilylpropylmethacrylate and octamethylcyclotetrasiloxane is (8-10):(1-3):(1-3):
3.
4. The modified graphene silane composite binder according to claim 1 or 2, characterized in that: The fluorinated silane is 3-fluoropropyltrimethoxysilane.
5. The modified graphene silane composite binder according to claim 1 or 2, characterized in that: The conductive agent includes reduced graphene oxide and carbon nanotubes, and the mass ratio of the two is (4-6): (1-2).
6. The modified graphene-silane composite binder according to claim 5, characterized in that: The particle size of the reduced graphene oxide is 0.5-5 μm.
7. The modified graphene-silane composite binder according to claim 5, characterized in that: The diameter of the carbon nanotube is 1-50 nm.
8. The modified graphene-silane composite binder according to claim 1 or 2, characterized in that: The solvent includes at least one of n-heptane and ethyl acetate; Preferably, the solvent is a mixed solution of n-heptane and ethyl acetate, and the mass ratio of the two is (50-60): (50-40)。 9. The method for preparing the modified graphene silane composite binder according to any one of claims 1 to 8, characterized in that: The steps include: Mixing the silane coupling agent, the fluorinated silane, the conductive agent and the remaining amount of the solvent to obtain the modified graphene silane composite binder; Preferably, the mixing method is ultrasonic dispersion, the frequency of the ultrasonic dispersion is 5 to 20 KHz, and the time of the ultrasonic dispersion is 1 to 3 hours.
10. Use of the modified graphene-silane composite adhesive according to any one of claims 1 to 8 or the modified graphene-silane composite adhesive obtained by the preparation method according to claim 9 in metal bonding.
Citation Information
Patent Citations
Silicone adhesive composition, a method for the preparation thereof and an adhesive film
CA2885946A1
Method for preparing graphene / silicone rubber material from silane-modified graphene
CN106398223A
Epoxy modified organic fluorosilicone conductive sealing adhesive and preparation method thereof
CN118085809A
Graphene conductive paste with good dispersibility and preparation method thereof
CN119008081A
Conductive silicone rubber compositions and cured products thereof with improved oil resistance
KR1020090105986A